2020
DOI: 10.3390/membranes10120411
|View full text |Cite
|
Sign up to set email alerts
|

Some Critical Remarks about Mathematical Model Used for the Description of Transport Kinetics in Polymer Inclusion Membrane Systems

Abstract: Two kinetic models which are applied for the description of metal ion transport in polymer inclusion membrane (PIM) systems are presented and compared. The models were fitted to the real experimental data of Zn(II), Cd(II), Cu(II), and Pb(II) simultaneous transport through PIM with di-(2-ethylhexyl)phosphoric acid (D2EHPA) as a carrier, o-nitrophenyl octyl ether (NPOE) as a plasticizer, and cellulose triacetate (CTA) as a polymer matrix. The selected membrane was composed of 43 wt. % D2EHPA, 19 wt. % NPOE, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The usefulness of two kinetic models, proposed by Danesi [ 27 ] and Szczepanski [ 28 ], in the metal transport description was evaluated. According to the Danesi model, the ion transport can be described with a first-order kinetic reaction (Equation (1)) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The usefulness of two kinetic models, proposed by Danesi [ 27 ] and Szczepanski [ 28 ], in the metal transport description was evaluated. According to the Danesi model, the ion transport can be described with a first-order kinetic reaction (Equation (1)) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Model proposed by Szczepanski (Equation (2)) takes into account the volume of the feed phase and the membrane area and assumes reaching the equilibrium state of the system. Such an approach made it possible to estimate more accurately, compared to the Danesi model, the values of the initial fluxes of selected metal ions in transport through the PIM with a commercial carrier di-(2-ethylhexyl)phosphoric acid [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was previously shown that the transport of Cd(II), Zn(II), Pb(II), and Cu(II) ions through PIMs containing reactive ionic liquids or D2EHPA (di-(2-ethylhexyl)phosphoric acid) as a carrier obeys the kinetic laws of a reversible first-order reaction [ 18 , 19 ]: …”
Section: Introductionmentioning
confidence: 99%
“…Various studies have used the carrier di-(2-ethylhexyl) phosphoric acid (D2EHPA) incorporated in PIMs for the transport of divalent metals, such as Zn and Cu. Szczepanski evaluated the simultaneous transport of Zn, Cd, Cu, and Pb through a PIM consisting of 38% CTA, 43% D2EHPA, and 19% of the plasticizer 2-nitrophenyloctyl ether (NPOE) using a 0.5 M HNO 3 solution as a receiving phase [14]. A PIM made of 60% PVC and 40% D2EHPA was also the basis of a new passive sampler developed to measure Zn ion in urban waters [15].…”
Section: Introductionmentioning
confidence: 99%